A review on artificial intelligence for the diagnosis of fractures in facial trauma imaging - Pham, Tuan D.; Holmes, Simon B.; Coulthard, Paul (Frontiers in Artificial Intelligence, 2024)
Patients with facial trauma may suer from injuries such as broken bones, bleeding, swelling, bruising, lacerations, burns and deformity in the face. Common causes of facial-bone fractures are the results of road accidents, violence, and sports injuries. Surgery is needed if the trauma patient would be deprived of normal functioning or subject to facial deformity based on ndings from radiology. Although the image reading by radiologists is useful for evaluating suspected facial fractures, there are certain challenges in human-based diagnostics. Articial intelligence (AI) is making a quantum leap in radiology, producing signicant improvements of reports and workows. Here, an updated literature review is presented on the impact of AI in facial trauma with a special reference to fracture detection in radiology. The purpose is to gain insights into the current development and demand for future research in facial trauma. This review also discusses limitations to be overcome and current important issues for investigation in order to make AI applications to the trauma more eective and realistic in practical settings. The publications selected for review were based on their clinical signicance, journal metrics, and journal indexing.